Peran Akuntansi Manajemen Dalam Mengoptimalkan Struktur Biaya Pada UMKM Di Era Digital - Nilam Ayuningtyas; Purwanti, Purwanti (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to explore the role of management accounting information systems (SIAM) in optimizing the financial performance of micro, small, and medium enterprises (MSMEs) in the digital era. With the rapid advancement of digital technology, MSMEs in Indonesia face challenges in cost management and strategic decision-making. The research method used is qualitative, with literature analysis and literature studies from various sources. The results showed that the application of management accounting among MSMEs is still low, with many owners not understanding the concepts and benefits. Techniques such as cost-volume-profit analysis, budgeting, and cost control have not been applied optimally. Key challenges faced include lack of knowledge, limited resources, and access to technology. Recommendations to improve the application of management accounting in MSMEs include training and education, information system development, and policy support from the government. This research is expected to provide useful insights for MSME owners, accounting practitioners, and policy makers in improving the sustainability and performance of the MSME sector in Indonesia.